"Constructing Music" by Teresa Nakra. Book review. - Jorge E Variego (Journal of the Association for Technology in Music Instruction, 2025)
Technology is a crucial tool for enhancing music creativity and pedagogy, enriching learning rather than posing a threat to traditional educational means. The integration of computers into music pedagogy allows educators to access numerous resources, refining teaching methodologies and inspiring students' musical pursuits. Embracing technology in music education enables dynamic exploration of composition, production, and performance, fostering an interactive and engaging learning environment. Computers and AI offer opportunities for revitalizing music instruction and deepening students' appreciation for the art form. Teresa M. Nakra's Constructing Music presents an innovative approach to music theory instruction by substituting traditional Western notation with principles of computer programming. Through illustrative examples, the book guides learners in studying and making music using Max, advancing from basic to complex structures. Nakra's fusion of music theory and programming offers a fresh perspective, encouraging lateral thinking and creative exploration. By bridging object-oriented programming in Max with music theory, the book provides an inclusive approach to music education, empowering students to engage deeply with music through technology.
Keywords: music technology theory computers in music education